Empowerment and threat in response to mass protest shape public support for a social movement and social change: A panel study in the context of the Bersih movement in Malaysia. (13th June 2018) - Selvanathan, Hema Preya; Lickel, Brian
Abstract: One path to social change is through sustained collective action. Although such actions often explicitly target the public audience to raise support for a movement's cause, we know little about how the public psychologically responds to protests. To examine this question, a sample of Malaysians was surveyed before and immediately after the occurrence of mass street protests in Malaysia ( N  =   422) using a two‐wave longitudinal design. Analyses revealed that (beyond pre‐existing levels of movement identity and support for social change) experiencing empowerment in response to the protests promoted a supportive movement identity and more support for social change after the protests, whereas experiencing threat in response to the protests promoted an oppositional movement identity and less support for social change after the protests. This research suggests that the psychological impact of ongoing protests on the public can determine subsequent public support for the movement and its goals.